But let your ‘Yes’ be ‘Yes,’ and your ‘No,’ ‘No.’ Meaning construction in medical encounters - Eszter Kárpáti; Judit Kleiber (LingBaW)
This paper investigates interpretation in medical context. Our question is how institutional context influences the utterance meaning: if it is really triple layered (literal, utterance-type or pragmatic, Levinson 2000), or rather a continuum (Wilson 2016). Even idiomatic language use (Kecskes 2017) can induce uncertainty and obscurity, which can be and has to be solved in the given dialogue or discourse context (Wilson and Kolaiti 2017). The paper analyzes various medical encounters in a formal pragmasemantic model called ÂeALIS (Alberti and Kleiber 2014). The benefit of applying this system is that it represents the interlocutors’ mental states (beliefs, desires, and intentions) supplemented by the parameter of authority, by which the occurring mismatches can be captured formally. We have found that two main types of mismatch can be differentiated, and both of them can be originated from the fact that the context is not the same for the participants. Our findings support the view that meaning construction is rather flexible and context-sensitive: it can be considered as wandering along the meaning continuum without any clues.